Taxonomic revision of Chamaecrista sect. Absus subsect. Absus (Leguminosae, Caesalpinioideae) with adjustments in the new classification - Souza, Alessandro Oliveira De; Guarda Cavalcante, Raphael; José Da Silva, Marcos (Phytotaxa, 2022)
Chamaecrista, one of the largest genera of Leguminosae with 364 species, had its infrageneric classification recently redefined based on phylogenetic studies, and is now divided into four sections and three subsections. The section Absus, which now includes the section Grimaldia, was subdivided into three subsections: Viscosa, Zygophyllum and Absus, the latter being revised here due to several taxonomic and nomenclatural adjustments that are necessary. Such review resulted from study of specific literature, analysis of ca. 2000 collections of herbariums, including all type collections and expeditions to collect and observe specimens in field. We recognized 18 species to subsection Absus, a new one combination (Chamaecrista major), nine synonymizations and two lectotypifications. The review contains a morphology study of the section and species, an identification key to species, descriptions, illustrations, photographs, maps, updated nomenclature, conservation status, phenology for all species.